OPTIMASI PARAMETER PROSES PEMBUATAN BIOETANOL SORGUM DAN PENGARUH TERHADAP UNJUK KERJA MOTOR BENSIN - Sutrisno, Teng; Anggono, Willyanto; Lay, Kurniawaan; Simanjuntak, Melvin Emil (Otopro, 2021)
Bioethanol is a renewable fuel that resembles gasoline, bioethanol is produced from fermentation and distillation processes. One of the raw materials that produce bioethanol is Sorghum. Sorghum was chosen because it is superior to other plants. This study aims to analyze fermentation longtime and enzyme composition for the best composition to produce bioethanol from sorghum, and determine the quality of sorghum bioethanol. This research Sorghum bioethanol produced with an alcohol content of 94%. The test and analysis variables used were 31 samples. The results of this study are as follows : The best fermentation time is 4 days, the enzyme and yeast variable for the most volume of alcohol is 7% yeast 5% enzyme, the enzyme and yeast variable for the highest alcohol content is 7% yeast 7% enzyme. Laboratory test results when compared with PERTAMINA's standard regulations, especially Pertalite RON 90, Several parameters have rejected the regulations. Therefore sorghum bioethanol is used as an additive for Gasoline. Sorghum bioethanol is made addictive to gasoline RON 90, namely B10 (bioethanol sorghum 10%) and B20 (bioethanol sorghum 20%). It would cause an increase in the performance of gasoline engines.